GAGASAN PAN ISLAMISME SAYYID MUHAMMAD RASYID RIDA DALAM TAFSIR AL-MANAR, SATU HURAIAN - Abdullah, Mustaffa (Journal of Al-Tamaddun, 2005)
Pan Islamism was a great idea pioneered and promoted by Sayyid Jamal al-Din al-Afghani. Later, it was developed and propagated by other reformists such as Sayyid Muhammad Abduh and Sayyid Muhammad Rasyid Rida in their works. Therefore, the article in one hand will elucidate the main ideas of Sayyid Muhammad Rasyid Rida in his Tafsir al-Manar with regard to Pan Islamism. The discussion will be emphasized on the unity of ummah, religion, law, language and equality. In other hand, this article will advance the difficulties faced by Sayyid Muhammad Rasyid Rida in order to make his idea of Pan Islamism as a reality and success.